2006
DOI: 10.1088/0953-8984/18/47/002
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and magnetic behaviour of an Fe3O4nanotube array

Abstract: An Fe3O4 nanotube array was successfully prepared in pores of an anodic aluminium oxide (AAO) template. Fe3O4 nanotubes and the nanotube array were characterized by transmission and scanning electron microscopy. The average diameter of the nanotubes was about 200 nm, and the length was more than 10 µm. The static distribution of the magnetic moments was investigated by means of magnetostatic energy analysis and Mössbauer spectrum measurement. The resulting Mössbauer spectrum shows that the distribution of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…As seen in Fig. 8 and 9, a high magnetic field does not saturate the magnetization of the nanotube samples; this situation is similar to that reported previously in the case of iron oxide 55 and spinel ferrite 33,54 and can be presumably ascribed to the surface disorder of the magnetic spins in these nanotubular structures. The values of the coercivity and squareness for the Co 0.32 Fe 2.68 O 4 nanotubes with different wall thicknesses are presented in Table 1.…”
supporting
confidence: 89%
“…As seen in Fig. 8 and 9, a high magnetic field does not saturate the magnetization of the nanotube samples; this situation is similar to that reported previously in the case of iron oxide 55 and spinel ferrite 33,54 and can be presumably ascribed to the surface disorder of the magnetic spins in these nanotubular structures. The values of the coercivity and squareness for the Co 0.32 Fe 2.68 O 4 nanotubes with different wall thicknesses are presented in Table 1.…”
supporting
confidence: 89%
“…A survey of the literature reveals that a systematic method of preparation of nanotubes and elucidation of growth mechanism is largely elusive. 3,20 Electrodeposition over a nanoporous membrane is a simple, low-cost, and ingenious technique for the preparation of onedimensional structure with high purity. The ability of this technique to tune the material properties by controlling the length and diameter makes it promising for nanoscale material fabrication as an alternative to more expensive techniques such as molecular beam epitaxy and microlithography.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to 2-dimensional epitaxial films and zero-dimensional nanaoparticles it has recently been demonstrated that fabrication of 1-dimensional nanowires, nanorods and nanotubes is possible using porous polymer or anodized alumina templates [119][120][121]. These structures are far less explored than the film or nanoparticulate systems, and only few reports exist on magnetoresistance of magnetite nanowires which is of the order of 7% at room temperature [122,123].…”
Section: Magnetite Nanowiresmentioning
confidence: 99%